2015
DOI: 10.1063/1.4905301
|View full text |Cite
|
Sign up to set email alerts
|

The statistical behaviour of attached eddies

Abstract: Townsend's attached eddy hypothesis forms the basis of an established model of the logarithmic layer in wall-bounded turbulent flows in which this inertially dominated region is characterised by a hierarchy of geometrically self-similar eddying motions that scale with their distance to the wall. The hypothesis has gained considerable support from high Reynolds number measurements of the second-order moments of the fluctuating velocities. Recently, Meneveau and Marusic ["Generalized logarithmic law for high-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…Using this, Woodcock & Marusic (2015) showed that the log-law for the flow profile follows from Campbell's theorem.…”
Section: The Attached-eddy Hypothesis and Higher-order Momentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Using this, Woodcock & Marusic (2015) showed that the log-law for the flow profile follows from Campbell's theorem.…”
Section: The Attached-eddy Hypothesis and Higher-order Momentsmentioning
confidence: 93%
“…M. de Silva, I. Marusic, J. D. Woodcock and C. Meneveau The derivation of the structure functions is analogous to that presented by Woodcock & Marusic (2015) for the moments of the velocity. The details of this derivation can be found in appendix A.…”
Section: The Attached-eddy Hypothesis and Higher-order Momentsmentioning
confidence: 97%
See 3 more Smart Citations